Search for new resonances decaying to a $W$ or $Z$ boson and a Higgs boson in the $\ell^+ \ell^- b\bar b$, $\ell ν b\bar b$, and $ν\bar{ν} b\bar b$ channels with $pp$ collisions at $\sqrt s = 13$ TeV with the ATLAS detector - ATLAS collaboration (2859 authors) (2017)
A search is presented for new resonances decaying to a $W$ or $Z$ boson and a Higgs boson in the $\ell^+ \ell^- b\bar b$, $\ellν b\bar b$, and $ν\bar{ν} b\bar b$ channels in $pp$ collisions at $\sqrt s = 13$ TeV with the ATLAS detector at the Large Hadron Collider using a total integrated luminosity of 3.2 fb$^{-1}$. The search is conducted by looking for a localized excess in the $WH$/$ZH$ invariant or transverse mass distribution. No significant excess is observed, and the results are interpreted in terms of constraints on a simplified model based on a phenomenological Lagrangian of heavy vector triplets.